Structure-Based Design of 5-Methylpyrimidopyridone Derivatives as New Wild-Type Sparing Inhibitors of the Epidermal Growth Factor Receptor Triple Mutant (EGFR L858R/T790M/C797S ) - Shen, Jiayi; Zhang, Tao; Zhu, Su-Jie; Sun, Min; Tong, Linjiang; Lai, Mengzhen; Zhang, Rong; Xu, Wei; Wu, Ruibo; Ding, Jian; Yun, Cai-Hong; Xie, Hua; et al. (Journal of medicinal chemistry, 2019)
Tertiary EGFRc797s mutation induced resistance against osimertinib (1) is an emerging "unmet clinical need" for non-small-cell lung cancer (NSCLC) patients. A series of 5-methylpyrimidopyridone derivatives were designed and synthesized as new selective EGFR(L858R/T790M/C797S) inhibitors. A representative compound, 8r-B, exhibited an ICso of 27.5 nM against the EGFR(L858R/T790M/C797S) mutant, while being a significantly less potent for EGFRwr (IC50 > 1.0 NM). Cocrystallographic structure determination and computational investigation were conducted to elucidate its target selectivity.